2020
DOI: 10.1080/07420528.2020.1756841
|View full text |Cite
|
Sign up to set email alerts
|

Does the compromised sleep and circadian disruption of night and shiftworkers make them highly vulnerable to 2019 coronavirus disease (COVID-19)?

Abstract: Rotating and permanent night shiftwork schedules typically result in acute and sometimes chronic sleep deprivation plus acute and sometimes chronic disruption of the circadian time structure. Immune system processes and functionalities are organized as circadian rhythms, and they are also strongly influenced by sleep status. Sleep is a vital behavioral state of living beings and a modulator of immune function and responsiveness. Shiftworkers show increased risk for developing viral infections due to possible c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 118 publications
(148 reference statements)
4
45
0
2
Order By: Relevance
“…Accordingly, recent studies reported that individuals are waking up and sleeping later during the confinement, possibly influenced by the increased use of digital media near bedtime [ 1 ]. Also, reduced exposure to the sunlight, limited activity during the day, and alterations in the food time may lead to dysregulation in the circadian rhythms and, in consequence, may affect sleep [ 2 , 3 ]. Furthermore, sleep quality is closely related to the mood, which was demonstrably altered during this time [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, recent studies reported that individuals are waking up and sleeping later during the confinement, possibly influenced by the increased use of digital media near bedtime [ 1 ]. Also, reduced exposure to the sunlight, limited activity during the day, and alterations in the food time may lead to dysregulation in the circadian rhythms and, in consequence, may affect sleep [ 2 , 3 ]. Furthermore, sleep quality is closely related to the mood, which was demonstrably altered during this time [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A higher incidence and severity of respiratory infections has been reported among night shift workers [12]. These ndings support a signi cant relationship between disrupted circadian rhythms and an individual's increased vulnerability to infectious diseases and suggest that excess risk could also be observed among individuals with high LAN exposures for the infection of COVID-19 [2], a coronavirus causing the global pandemic in 2020.…”
Section: Introductionmentioning
confidence: 61%
“…Furthermore, some evening-oriented individuals may be healthcare workers and thus can better adjust to the night-time work shift, enabling them to keep saving lives while others cannot function properly (e.g., Silva et al, 2017;Hittle and Gillespie, 2018). However, sleep deprivation interferes with immunity and self-regulation (Shields et al, 2017;Rantala et al, 2021), which might increase the risk of contamination with the new coronavirus, increasing shift workers' vulnerability especially in the healthcare frontline tackling the pandemic (Silva et al, 2020). Thus, not all eveningoriented individuals are a liability or non-compliant with the pandemic safety measures.…”
Section: Discussionmentioning
confidence: 99%